The soundscape of Pasolini's Gospel According to St. Matthew - Martellozzo, Nicola (Journal for religion, film and media, 2019)
Il Vangelo Secondo Matteo (1964), by the Italian film director Pier Paolo Pasolini, is one of the most interesting and widely acclaimed film representations of the life of Jesus. Its reception in the Catholic world has reflected the alternating fortunes of Pasolini himself, but over the years critics have come to fully appreciate its merits. While the director made faithful use of the dialogues in the Gospel, he constructed a new - but plausible - imagination, or "architecture of reality", based on an intertextual code with intersecting pictorial, architectural, biblical and sound references. This essay aims in particular to employ a semiotic approach to analyse the musical motifs in the film, and the way in which they convey precise meanings and values to the viewer about the figure and life of Jesus. Songs and musical compositions are leitmotifs that punctuate the narrative, interweaving with the visual component to form a full-blown language in its own right.